ERTIMO APP: MENINGKATKAN KUALITAS PEMBELAJARAN LITERASI AWAL DENGAN APLIKASI REKOMENDASI PEMBELAJARAN - Andriningrum, Hana; Ardhyantama, Vit; Novitasari, Welly; Imaduddin, Muhammad; Malik, Muh Syauqi; Wati, Ika Febriana; Wardani, Helda Kusuma; Indrawati, Delia (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The aim of this study was to develop and evaluate the ERTIMO application, a learning recommendation tool designed to enhance the quality of early Indonesian literacy instruction conducted by teachers. Utilizing the ADDIE (Analysis, Design, Development, Implementation, Evaluation) instructional design model, ERTIMO's content was systematically curated through an extensive literature review. The application's feasibility and effectiveness were assessed through expert validations and field trials, employing observations, assessment scales, running records, and writing assignments. Statistical analysis via T-tests confirmed that ERTIMO significantly improved learning quality, particularly in teacher engagement, student participation, and the utilization of learning media, while aspects such as instructional material and learning environment remained largely unchanged. The novelty of ERTIMO lies in its integration of a recommender system to assist teachers in organizing instruction, addressing the prevalent issue of inadequate strategy adoption in early reading and writing literacy for early elementary school class.